Notes on Horses and Dogs: Two Special Animals? - Battini, Laura (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2021)
Animals have shaped the daily life of people in Mesopotamia much more so than ours: two of the animals for which man has felt a real friendship, the dog and the horse, are here analysed. Why analyse together these two animals which seem so different? Because only for them has man used the most important human rite, the burial.